2023
DOI: 10.3389/fenrg.2022.957032
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous electrode materials for supercapacitor: Preparation and surface functionalization

Abstract: Supercapacitors became more and more important recently in the area of energy storage and conversion. Their large power deliveries abilities, high stability and environmental friendliness characteristics draw tremendous attention in high-power applications such as public transit networks. Carbonaceous materials with unique surface and electrochemical properties were widely used in supercapacitors as electrode materials. This review focuses on the developments in supercapacitor electrodes made from carbonaceous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…Several studies have shown that metal compound-based pseudocapacitive electrode materials perform well in terms of multiplicity and cycle stability, although carbon bilayer electrode materials' specific capacitance is poor. [84][85][86][87][88][89] Therefore, the primary challenge in SCs development aims to design and synthesize electrode materials with high specific capacity, high multiplicity performance, and long cycle stability. To compensate for this deficiency, composites can be considered to be designed excellent electrochemical performance by exploiting the synergistic effect between various electrode materials.…”
Section: Composite Materials Optimizationmentioning
confidence: 99%
“…Several studies have shown that metal compound-based pseudocapacitive electrode materials perform well in terms of multiplicity and cycle stability, although carbon bilayer electrode materials' specific capacitance is poor. [84][85][86][87][88][89] Therefore, the primary challenge in SCs development aims to design and synthesize electrode materials with high specific capacity, high multiplicity performance, and long cycle stability. To compensate for this deficiency, composites can be considered to be designed excellent electrochemical performance by exploiting the synergistic effect between various electrode materials.…”
Section: Composite Materials Optimizationmentioning
confidence: 99%
“…Exhaustion of fossil fuels, increased energy consumption, severe environment pollution as well as global warming effects threatening the sustainability of living standards. Therefore, exploring and developing new technologies for energy conversion and storage become increasingly important [1,2] . Renewable energy sources (solar, tidal and wave energy, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exploring and developing new technologies for energy conversion and storage become increasingly important. [1,2] Renewable energy sources (solar, tidal and wave energy, etc.) can serve as alternative energy sources to meet people's energy needs, but it is hard for them to provide stable energy demand directly because of their inconsistencies caused by seasonal and regional variations.…”
Section: Introductionmentioning
confidence: 99%